Is the "new normal" a return to inertia and inequalities?. Issue 3 (1st December 2022) - Koff, Harlan; Maganda, Carmen; Kauffer, Edith; Ros Cuellar, Julia; González Hernández, Citlalli Alhelí
Abstract : Since 2020, the editorial team at Regions & Cohesion has engaged these editors' notes as a way to highlight the relevance of the socio-economic research published in the journal for our understanding of current events. We have specifically embraced discussions on the COVID-19 pandemic from the point of view of the social construction of vulnerability and risk. Our editors' notes have focused on the relationship between development strategies and the health and economic impacts of the pandemic, and we have contextualized these discussions by focusing on global inequalities and their local manifestations. Like many people, our fear has been (and continues to be) that a "return to normal" represents a return to unsustainable development and inequity.